Дослідження та апроксимація функції визначення допустимих середніх квадратичних похибок площ земельних ділянок - Рябчій, В. В.; Трегуб, М. В. (Видавництво Львівської політехніки, 2012)
Исследованы зависимости средних квадратических ошибок определения площадей земельных участков от величин этих площадей и коэффициентов вытянутости. Используя полученные данные, выполнена аппроксимация средних квадратических ошибок площадей в промежутках 0,1–1 га, 1–10 га и 10–100 га квадратической функцией и ее оценка точности. Were researched dependences of standard mean square errors of land parcel area determination as a function of area and elongation coefficients. Using investigated values was made an approximation of quadratic polynomial function for standard mean square errors of land parcel area in intervals 0,1-1 he, 1-10 he, 10-100 he with evaluation of accuracy of approximated functions.